ISLAM AND SCIENCE: AN ANALYSIS OF THE GOLDEN AGE OF ISLAM IN THE FIELD OF SCIENCE AND TECHNOLOGY, ESPECIALLY IN THE FIELD OF MANAGEMENT - Efa Nurazizah (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2026)
This article explains the position of science in Islam. Science and Islam are a duality. Islam once lived through a period of rapid scientific and technological development, with its influence reaching across Europe and the world. To this day, the scientific products of that era remain a global reference, and their stories are immortalized in scientific forums both eastern and western. A vast body of literature chronicles and analyzes the golden age of civilization. In Islam, science is equated with the Quran, for all knowledge originates from it. Numerous verses in the Quran and Hadith explain the importance of seeking knowledge and its virtues. Unfortunately, the dichotomy of knowledge has led some to believe that there are obligatory and optional sciences to be studied. This has weakened Muslim human resources, especially in responding to the challenges of the times, where science, technology, and the arts continue to develop. This article aims to contribute knowledge that openness to absorbing knowledge has a significant impact on the advancement of civilization. Eliminate the dichotomy of knowledge and avoid being allergic to new sciences that lack Islamic labels. The source of knowledge is, in essence, the Quran.